2011
DOI: 10.1258/ar.2011.110021
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic characteristics of sinonasal fungus ball: an analysis of 119 cases

Abstract: When there are no calcifications visible on the CT scan, a hyperattenuating fungal ball located in the central area of the sinus with mucosal thickening on enhanced CT scans is an important feature of a non-invasive sinonasal fungus ball. On MRI, a sinonasal fungus ball has typical features of a marked hypointense fungus ball with a hyperintense mucosal membrane in T2-weighted images. A contrast-enhanced CT scan or MRI provides sufficient information for the preoperative differentiation of a sinonasal fungus b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 16 publications
(16 reference statements)
5
50
0
1
Order By: Relevance
“…Computed tomography (CT) of the sinuses is the first choice for preoperative diagnosis of chronic rhinosinusitis and for planning ESS because of its ability to delineate the fine bone structures of the sinuses, orbital lamina, and skull base . Several studies have reported the CT features of MSFB, which include intralesional hyperdensity (IH), calcification spots, erosion of the inner sinus wall, irregular surface of the material, and sclerosis of the lateral sinus wall …”
Section: Introductionmentioning
confidence: 99%
“…Computed tomography (CT) of the sinuses is the first choice for preoperative diagnosis of chronic rhinosinusitis and for planning ESS because of its ability to delineate the fine bone structures of the sinuses, orbital lamina, and skull base . Several studies have reported the CT features of MSFB, which include intralesional hyperdensity (IH), calcification spots, erosion of the inner sinus wall, irregular surface of the material, and sclerosis of the lateral sinus wall …”
Section: Introductionmentioning
confidence: 99%
“…In a previoius study (13), the prevalence of intrasinus calcifications on CT scans in patients with sinonasal fungus ball has been reported as 67.2% (116 cases). The calcifications were located mostly in the center of the maxillary sinus (85.9%), followed by near the sinus wall (7.7%).…”
Section: Discussionmentioning
confidence: 97%
“…4). 25,[27][28][29] Invasive Fungal Sinus Disease Magnetic resonance imaging plays a critical role in the diagnosis and management of invasive fungal sinus disease. Invasive fungal sinus disease carries a high likelihood of orbital, cavernous sinus, and intracranial involvement.…”
Section: Fungal Sinonasal Infectionmentioning
confidence: 99%